PCDH1 facilitates migration, proliferation, and stemness of pancreatic cancer cells through PI3K-Akt signaling - Yang, Zhiqiang; Zhang, Zhipeng; Song, Ye; Dai, Chuang; Zhang, Weihui; Zhao, Dali (Frontiers in Oncology, 2026)
BackgroundPancreatic ductal adenocarcinoma (PDAC) exhibits high lethality due to late diagnosis, therapy resistance, and cancer stem cell (CSC)-driven progression. However, the molecular determinants of stemness in PDAC remain unclear.MethodsWe integrated RNA-sequencing and clinical data from TCGA to calculate stemness indices and identify hub genes using weighted co-expression network analysis and differential expression profiling. PCDH1 expression was validated in PDAC tissues by qRT-PCR and immunohistochemistry. Functional assays, including MTT, colony formation, Transwell, wound healing, flow cytometry, and spheroid culture, were performed following PCDH1 knockdown. Transcriptome sequencing was used to delineate downstream signaling mechanisms.ResultsPCDH1 emerged as a stemness-associated oncogene strongly linked to poor survival. It was markedly overexpressed in PDAC tissues and cell lines. Silencing PCDH1 significantly impaired proliferation, clonogenicity, migration, and CSC frequency. Sphere-forming ability was also reduced. Transcriptomic analysis revealed downregulation of PI3K/AKT signaling upon PCDH1 knockdown, and rescue experiments confirmed its role in driving PDAC progression through PI3K/AKT activation. High PCDH1 expression further correlated with immune exclusion and distinctive patterns of chemosensitivity.ConclusionPCDH1 is a novel stemness-linked oncogene that accelerates PDAC progression via PI3K/AKT signaling. Its prognostic relevance, association with immune evasion, and impact on drug responsiveness highlight PCDH1 as a promising biomarker and therapeutic target for CSC-directed intervention in PDAC.